2021
DOI: 10.3389/fgene.2021.717294
|View full text |Cite
|
Sign up to set email alerts
|

A Founder Pathogenic Variant of PPIB Unique to Chinese Population Causes Osteogenesis Imperfecta IX

Abstract: Background: Osteogenesis imperfecta (OI) is a heterogeneous genetic disorder characterized by bone fragility. PPIB pathogenic variants cause a perinatal lethal form of OI type IX. A limited number of pathogenic variants have been reported so far worldwide.Methods: We identified a rare pedigree whose phenotype was highly consistent with OI-IX. Exome sequencing was performed to uncover the causal variants. The variant pathogenicity was classified following the ACMG/AMP guidelines. The founder effect and the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Therefore, we cannot rule out a founder effect of this mutation in Chinese population or a relatively isolated region subjectively. Furthermore, the AF and incidence of this BBS1 variant can be estimated within large scale exon data and confirmed whether it was a founder mutation or do haplotype analysis and mutation dating as follow-through (Zhu et al, 2021). The identification of ethnic specific founder mutation can help to determine screening strategy for disease prevention and facilitate genetic counseling.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, we cannot rule out a founder effect of this mutation in Chinese population or a relatively isolated region subjectively. Furthermore, the AF and incidence of this BBS1 variant can be estimated within large scale exon data and confirmed whether it was a founder mutation or do haplotype analysis and mutation dating as follow-through (Zhu et al, 2021). The identification of ethnic specific founder mutation can help to determine screening strategy for disease prevention and facilitate genetic counseling.…”
Section: Discussionmentioning
confidence: 74%
“…As one of the Wnt gene family, activation of Wnt10a promoted osteogenesis-related pathways in BMSCs [ 57 ]. As one of the genes encoding peptidylprolyl isomerase B (PPIB), Snx22 downregulation was associated with Osteogenesis Imperfecta, Type Ix and Brittle Bone Disorder [ 58 ]. These results indicated that it is the NIR irradiation mode but not the NIR irradiation itself that contributed to the gene expression pattern alterations of BMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Type VI OI is characterized by abnormal bone mineralization and the presence of ichthyosis-like bone buildup in the bone tissue. Patients with type VII OI are more likely to exhibit short humerus and femurs, brittle bones, and skeletal abnormalities, while those with type VIII OI face significant challenges in bone formation and mineralization. , Type IX may manifest bowed limbs, spinal curvature, and other progressive bone abnormalities. A distinctive characteristic of this subtype is the presence of white sclera, often observed in individuals with type IX. The exceptionally rare type X presents clinical symptoms such as hydrocephalus, widespread bone loss leading to diminished muscular strength, and thoracic scoliosis …”
Section: Oi Typologymentioning
confidence: 99%
“…Deficits in CyPB can result in reduced 3-prolyl hydroxylation and post-translational over-modification. Recent studies have shown that mutations in PPIB lead to type IX OI, this outcome is attributed to the disruption of the function of the P3H1/CRTAP/CyPB complex. , Understanding the intricate interactions within this complex is crucial for unraveling the molecular mechanisms underlying type IX OI and advancing potential therapeutic interventions.…”
Section: Oi Pathogenesismentioning
confidence: 99%